Meningkatkan Hasil Belajar Geografi Dengan Menggunakan Media Pembelajaran Powerpoint Pada Materi Dinamika Litosfer di Kelas X IPS 2 SMA Negeri 1 Baubau - Irwan, Irwan; Harudu, La (UNM Geographic Journal, 2019)
SMAN 1 Baubau is one of the schools in Baubau City, Bataraguru Village, which is the object of research by researchers because its learning outcomes are still low, this is because only 38% of them meet the KKM. The objectives of the study were: (1) to find out the learning activities of students of class X IPS2 and teaching activities of teachers of SMAN 1 Baubau when applying powerpoint media, (2) to find out the geography learning outcomes of IPS X class 2 students of Baubau Public High School taught with powerpoint based learning media this is done in class X IPS2 of SMAN 1 Baubau even semester of school year 2018/2019, dated January 7 2019 to February 6, 2019. This type of research is classroom action research (PTK) which is conducted in two cycles. The subjects of this research are teachers and class students X IPS2 SMAN 1 Baubau. The data in the study are qualitative and quantitative data obtained from observation sheets and learning outcomes tests. From the analysis results, it can be concluded that by applying powerpoint media (1). Student learning activities increase with an average score of 3.1 categorized well. (2). Teacher teaching activities increased with an average score of 3.3 categorized well. (3). Geographical learning outcomes of students of class X IPS2 at SMAN 1 Baubau increased with an average score of 81, with 80% learning completeness or 35 students with a value of ≥ 72 according to KKM geography.SMAN 1 Baubau adalah salah satu sekolah di Kota Baubau Kelurahan Bataraguru yang menjadi objek penelitian peneliti karena hasil belajarnya yang masih rendah, hal ini disebabkan hanya 38% yang memenuhi KKM. Tujuan penelitian: (1)untuk mengetahui aktivitas belajar siswa kelas X IPS2 dan aktivitas mengajar guru SMAN 1 Baubau saat menerapkan media powerpoint,(2) untuk mengetahui hasil belajar geografi siswa kelas X IPS2 SMAN 1 Baunau yang diajarkan dengan media pembelajaran bebasis powerpoint.Penelitian ini dilakukan dikelas X IPS2 SMAN 14 Bombana semester genap tahun ajaran 2018/ 2019, tanggal 07 januari 2019 sampai dengan tanggal 6 februari 2019. Jenis peneliitian adalah penelitian tindakan kelas (PTK) yang dilaksanakan dengan dua siklus.Subjek penelitian ini adalah guru dan siswa kelas X IPS2 SMAN 1 Baubau. Data dalam penelitian adalah data kualitatif dan kuantitatif yang diperoleh dari lembar observasi dan tes hasil belajar. Dari hasil analisis diperoleh kesimpulan bahwa dengan menerapkan media powerpoint (1). Aktivitas belajar siswa meningkat dengan skor rata-rata 3,1 berkategorikan baik.(2). Aktivitas mengajar guru meningkat dengan skor rata-rata 3,3 berkategorikan baik.(3). Hasil belajar geografi siswa kelas X IPS2 SMAN 1 Baubau meningkat dengan skor rata-rata 81, dengan ketuntasan belajar 80% atau terdapat  35 siswa dengan nilai  ≥ 72 sesuai KKM geografi.